Research on Configuration of Single Motor Hybrid Transmission with Double Row Parallel Planetary Gear Mechanism - Jinxia Liu; Lei Liu; Aibo Wang; Le Geng (Jixie chuandong)
Based on the lever method， the possible connection schemes are obtained via matching the components of leverage node of double row parallel planetary gear mechanism （PGM）. A layout scheme with less linking elements and more gears is achieved by analyzing the arrangement of engine， motor and linking elements. According to the gear ratio range of existing double row parallel PGM transmissions， the PGM connection scheme is screened， and finally 17 configurations of SMT are obtained. Arbitrary selected a configuration of SMT and topologized， the operation mode and power flow of the configuration of SMT are analyzed. It is obtained that not only can it realize engine driving， motor driving， hybrid driving， driving power generation， braking power generation and parking power generation working modes， but also is no cycle power in each working mode.